Judicial Preview Oleh Mahkamah Konstitusi Sebagai Upaya Preventif Perlindungan Hak Konstitusional (Studi Komperasi Dengan Mahkamah Konstitusi Chili) - Sihaloho, Elisabeth; Wisnaeni, Fifiana (UI Scholars Hub, 2024)
The existence of the Constitutional Court as stated in the provisions of Article 24C of the 1945 Constitution has established the dignity of the Constitutional Court's position as a Guardian of the Constitution which is understood as a judicial institution that protects the constitutional rights of Indonesia citizens. This research is aimed at solving the problem of the constitutional rights of Indonesia citizens who are often injured through legal products in the form of laws. Therefore, this study focuses on studying, analyzing and comparing how the context of judicial preview or can be understood as a test of a draft law both formally and materially as a form of preventive protection of citizen’s constitutional rights. The writing of this journal is a normative juridical research based on a literature study by examining and understanding the basic mechanism regarding the provisions for testing laws in positive law in Indonesia accompanied by the act of analyzing the process of implementing judicial preview (testing of draft laws) carried out by the Chilli Constitutional Court. The final result of writing this journal is in the form of a prospective study of the expansion of the authority of the Constitutional Court of Indonesia in conducting a judicial preview (testing of draft laws) which can later be expected to be adopted in positive legal provisions.